Awareness and attitudes toward passive smoking: sociodemographic correlates and public health implications from a cross-sectional study in Saudi Arabia - Syed Khaja, Azharuddin Sajid; Alrashdi, Hamad Rudhayman; Almuzaini, Osama Abdullah; Alanzi, Hatim Salem; Alshuhail, Rabah Abdulaziz; Muzammil, Khursheed; Afreen, Sheeba; Saleem, Mohd (Frontiers in Public Health, 2025)
Background and AimPassive smoking, or secondhand smoke exposure, poses a major public health risk linked to various adverse outcomes. This study aimed to assess sociodemographic characteristics, exposure patterns, and levels of awareness and attitudes toward passive smoking among a group of volunteers in Saudi Arabia.MethodsA descriptive cross-sectional design was applied, with 301 participants enrolled through convenience sampling. The sample included members of the public and university students, including medical students, to enable educational-level comparisons. Individuals unwilling to participate, unable to provide consent, or unable to complete the survey were excluded. Data were obtained via a structured, pilot-tested questionnaire that assessed demographics, SHS exposure, knowledge, and attitudes. Reliability was confirmed (Cronbach's α = 0.78), and principal component analysis (PCA) was used to extract key awareness and attitude dimensions.ResultsThe study cohort was predominantly aged 18–30 years (65.1%), held college degrees (76.4%), and resided in urban areas (84.4%). While 84.1% were non-smokers, over one-third lived with smokers, and 42.5% reported weekly exposure, most often in public venues. Awareness of SHS risks was high: 94.4% recognized its harmful effects, and 89.0% identified children and pregnant women as particularly vulnerable. Support for smoke-free policies was also strong (85.7%). The PCA identified four components: general knowledge, advocacy, tolerance of smoking behavior, and perceptions of policy. Overall, 85.7% demonstrated good awareness and attitudes.ConclusionThis study highlights high awareness and strong support for smoke-free policies among participants. These findings support the need for continued education and stronger regulatory efforts to minimize passive smoke exposure, particularly in public areas.